2015
DOI: 10.1016/j.stemcr.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Activity and High-Order Effective Connectivity Alterations in Sanfilippo C Patient-Specific Neuronal Networks

Abstract: SummaryInduced pluripotent stem cell (iPSC) technology has been successfully used to recapitulate phenotypic traits of several human diseases in vitro. Patient-specific iPSC-based disease models are also expected to reveal early functional phenotypes, although this remains to be proved. Here, we generated iPSC lines from two patients with Sanfilippo type C syndrome, a lysosomal storage disorder with inheritable progressive neurodegeneration. Mature neurons obtained from patient-specific iPSC lines recapitulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 44 publications
(65 reference statements)
5
52
1
Order By: Relevance
“…Another study reported that heparan sulfate oligosaccharides were able to increase the formation of focal adhesions in mouse astrocytes and human neural progenitor cells, leading to cell polarization and migration defects [142]. These data are in line with changes of neuronal organization, effective connectivity, and spontaneous activity detected in MPS IIIC patient iPSC-derived neuronal progenitors [143].…”
Section: Specific Effects Of Heparan Sulfatesupporting
confidence: 65%
“…Another study reported that heparan sulfate oligosaccharides were able to increase the formation of focal adhesions in mouse astrocytes and human neural progenitor cells, leading to cell polarization and migration defects [142]. These data are in line with changes of neuronal organization, effective connectivity, and spontaneous activity detected in MPS IIIC patient iPSC-derived neuronal progenitors [143].…”
Section: Specific Effects Of Heparan Sulfatesupporting
confidence: 65%
“…We show an experimental application of our approach to spontaneously generated in vitro networks of human iPSC-derived neurons cultured on MEAs providing an analysis and interpretation of the physiology not possible otherwise. We describe the temporal evolution associated with the connectivity and dynamic signaling of developing hiPSC-derived neuronal networks, including increasing synchronized activity and the formation of small numbers of hyper-connected hub-like nodes, as similarly reported by others [14,20]. These results further support the performance quality of our approach and provide an example of how this connectivity method can be used to characterize network formation and dynamics, thus facilitating efforts to generate predictive models for neurological disease, drug discovery and neural network modeling.…”
Section: Figuresupporting
confidence: 53%
“…In humans, in the absence of intracranial recording electrodes, neither physiological nor pathological network activity can be studied in vivo. The introduction of human induced-pluripotent stem cell (hiPSC) technologies [12,13] opened the possibility to generate in-vitro neuronal networks in typical [14,15], as well as patient-specific genetic backgrounds [16,17,18,19,20,21], demonstrating the potential to reproduce key molecular and pathophysiological processes in highly controlled, reduced, experimental models that enables the study of neurological disorders and the discovery and testing of drugs, especially in the context of the individual patient [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In Sanfilippo disease (mucopolysaccharidosis III), there is an accumulation of heparan sulfate in the lysosomes due to an impaired function of one of several lysosomal enzymes. We have assayed the inhibition of the EXTL2 and EXTL3 genes, as a substrate reduction therapy for Sanfilippo C disease in patients' fibroblasts and we are currently performing a similar approach on Sanfilippo C neurons, derived from induced pluripotent stem cells (iPSC) generated by our group …”
Section: Osteochondromatosis or Multiple Hereditary Exostosismentioning
confidence: 99%
“…Our aim was to create osteoblasts derived from WT human iPSC generated in our group and compare them with those generated from GD patients (N370S/N370S, a gift from Ricardo Feldman, G202R/L444P, a gift from Gustavo Tiscornia, and N370S/84GG). For the MSC‐like cell induction, we used a multistep culture method, summarized in Figure A.…”
Section: Gaucher Diseasementioning
confidence: 99%